Texture and structure of the Late Holocene ground ice in the Northern West Siberia - Ya. V. Tikhonravova; E. A. Slagoda; V. V. Rogov; E. I. Galeeva; V. V. Kurchatov (Лëд и снег, 2017)
The Late Holocene ground ices are occurred due to freeze cracking, slope, thermocast, thermoerosion pro‑ cesses. New formation ice within may intervene to the Pleistocene, lower Holocene ground ice and perma‑ frost and can really complicate their structure. Relationship between seasonal and perennial new formation of ice with massive ice and permafrost was studied in cross section of the North Western Siberia. The features of texture and structure of ice formed in the thawing cavities, some cracks were determined. The differences in structure of the late Holocene ground ices and ground ices of the early Holocene and late Pleistocene were defined. The differences in ground ice texture and structure depend to the cavity configuration of the freezing and cracks and freezing temperature conditions. The quantitative parameters of the crystal structure can be used to identify closed‑cavity ice and crack ice in the composition of massive ice and determine mechanisms and conditions of formation before the Holocene ice wedges.